Implementasi Sistem Akuntansi Penggajian untuk Efektivitas Pengendalian Internal dan Manajemen SDM KSP Bangkit Usaha Mandiri Pamriyan - Sukemi Kamto Sudibyo; Eni Endaryati; Vivi Kumalasari Subroto; Sri Wahyuning; Erlinda Sahda Nurmala (MANAJEMEN, 2026)
This study aims to analyze and implement a payroll management accounting system to improve the effectiveness of internal control and human resource management at KSP Bangkit Usaha Mandiri Pamriyan. The problem faced is that the payroll process is still manual and not yet integrated, potentially leading to recording errors, delays in data processing, and a lack of information transparency. The research method used is Research and Development (R&D), with the stages of problem identification, data collection through interviews, observations, and literature review, system design, validation, and system testing. The results show that the implementation of a payroll management accounting system can improve the efficiency and accuracy of payroll data processing. The system also contributes to strengthening internal control through increased transparency and ease of monitoring. In human resource management, this system helps provide more accurate information as a basis for decision-making regarding employee management. Thus, the implementation of a payroll management accounting system has been proven to improve the effectiveness of internal control and support more optimal human resource management.